Identification the Factors that Influence Profit Persistence - Yogi Ginanjar; Risdayanti Risdayanti; Mazen Aditya Alnazar (DPPM Universitas Pelita Bangsa, 2023)
Profit quality is able to predict earnings in the future. Earnings persistence is an important topic of discussion because the information generated can be used by investors in determining earnings quality and firm value, thereby facilitating decision making. This study aims to determine the factors that influence profit persistence from the point of view of Audit Fee, Managerial Ownership and Institutional Ownership. The population of this study is all LQ45 companies registered at Indonesia Stock Exchange Period 2016-2022. Researchers used purposive sampling in the sampling technique so that 7 LQ45 companies were obtained with a total data of 49 data. The data used is secondary data. The analysis techniques in this study are descriptive analysis techniques, verification analysis with the classical assumption test, multiple linear analysis, analysis of the coefficient of determination, and hypothesis testing. The analytical tool in this study uses SPSS. The results of the study show that partially Audit Fee and Institutional Ownership has no effect on Profit Persistence, while Managerial Ownership has an effect on Profit Persistence. Simultaneously Audit Fees, Managerial Ownership and Institutional Ownership have no effect on Profit Persistence.